MCU proteins dominate in vivo mitochondrial Ca2+ uptake in Arabidopsis roots - Ruberti, Cristina; Feitosa-Araujo, Elias; Xu, Zhaolong; Wagner, Stephan; Grenzi, Matteo; Darwish, Essam; Lichtenauer, Sophie; Fuchs, Philippe; Parmagnani, Ambra Selene; Balcerowicz, Daria; Schoenaers, Sébastjen; Torre, Carolina de la; et al. (The plant cell, 2022)
Ca2+ signaling is central to plant development and acclimation. While Ca2+-responsive proteins have been investigated intensely in plants, only a few Ca2+-permeable channels have been identified, and our understanding of how intracellular Ca2+ fluxes is facilitated remains limited. Arabidopsis thaliana homologs of the mammalian channel-forming mitochondrial calcium uniporter (MCU) protein showed Ca2+ transport activity in vitro. Yet, the evolutionary complexity of MCU proteins, as well as reports about alternative systems and unperturbed mitochondrial Ca2+ uptake in knockout lines of MCU genes, leave critical questions about the in vivo functions of the MCU protein family in plants unanswered. Here, we demonstrate that MCU proteins mediate mitochondrial Ca2+ transport in planta and that this mechanism is the major route for fast Ca2+ uptake. Guided by the subcellular localization, expression, and conservation of MCU proteins, we generated an mcu triple knockout line. Using Ca2+ imaging in living root tips and the stimulation of Ca2+ transients of different amplitudes, we demonstrated that mitochondrial Ca2+ uptake became limiting in the triple mutant. The drastic cell physiological phenotype of impaired subcellular Ca2+ transport coincided with deregulated jasmonic acid-related signaling and thigmomorphogenesis. Our findings establish MCUs as a major mitochondrial Ca2+ entry route in planta and link mitochondrial Ca2+ transport with phytohormone signaling.